Staphylococcus aureus Clumping Factor A Remains a Viable Vaccine Target for Prevention of S. aureus Infection - Annaliesa S. Anderson; Ingrid L. Scully; Ed T. Buurman; Joseph Eiden; Kathrin U. Jansen (mBio, 2016)
ABSTRACT In a recent article, X. Li et al. [mBio 7(1):e02232-15, 2016, http://dx.doi.org/10.1128/mBio.02232-15] investigate the utility of a vaccine composed of the Staphylococcus aureus protein clumping factor A (ClfA) in protecting mice from S. aureus infection. ClfA, one of the first proteins to be identified as a potential vaccine antigen for S. aureus prophylaxis, is currently a component of several investigational vaccines. The authors conclude that ClfA may not be effective for S. aureus prophylaxis. In contrast, previously published papers reporting positive data suggested that ClfA was potentially an important vaccine target to prevent invasive S. aureus disease. This commentary addresses the observed differences between the findings of Li et al. and those from other publications, highlighting the importance for preclinical vaccine antigen assessments to reflect the biological role of said antigen in virulence and, consequently, the importance of choosing appropriate preclinical disease models to test such antigens.